Treatment of Hypertension in Renal Transplant Recipients in Four Independent Cross-Sectional Analyses - Izabella Kuźmiuk-Glembin; Dorota Adrych; Leszek Tylicki; Zbigniew Heleniak; Hanna Garnier; Jakub Wiśniewski; Przemysław Rutkowski; Bolesław Rutkowski; Alicja Dębska-Ślizień (Karger Publishers, 2018)
Background/Aims: This retrospective study analysed hypertension management and adherence to blood pressure (BP) targets among renal transplant recipients (RTRs) under specialized care in the Outpatient Transplantation Unit in the Department of Nephrology, Transplantology and Internal Medicine at Gdansk University Hospital. Methods: Medical records of 101, 316, 639 and 818 RTRs diagnosed with hypertension, who received outpatient care in 2001, 2006, 2011 and 2014, respectively were analysed in four independent cross-sectional surveys. All RTRs received antihypertensive regimens. Results: The overall most commonly used antihypertensive agents were beta-blockers (BB) (range 66.3-82.5%) followed by calcium channel blockers (CCB) (range 52.8-64.2%). Whilst a significant, upward tendency of BB usage (p<0.01) was observed, CCB usage (p<0.001) displayed a downward tendency as a first line therapy in the subsequent years. The average number of antihypertensive agents used per patient increased significantly from 2.24±1.03 in 2001 to 2.55±1.25 in 2014 (p<0.05). The most frequently used combination of hypotensive therapy consisted of two or three antihypertensive drugs depending on the survey. The most common two drug combination consisted of BB and CCB followed by BB accompanied by angiotensin converting enzyme inhibitors. A significant, upward tendency in the use of four (p<0.001) and five (p<0.05) antihypertensive drugs simultaneously, was observed in subsequent years. The target values of BP i.e. <140/90 mmHg were accomplished in 47, 58, 60 and 46% of RTRs in subsequent years. In a secondary - stratified analysis of data from 2014, younger patients (p<0.05), patients with better graft function (p<0.001), patients treated with a higher number of antihypertensive agents (p<0.001) and those not treated with BB (p<0.01) were shown to reach the BP target of below 140/90 mmHg more often. Conclusion: The study showed intensification of hypertension treatment in RTRs in subsequent years with BB assuming a dominant role.